Niemann-pick disease with visceral and pulmonary involvement in a resource limited setting: A rare case report - Eyasu Wakjira Korsa, MD; Samuel Sisay Hailu, MD; Hewan Asfaw, MD; Hanna Damtew, MD; Daniel Zewdneh Solomon, MD (Radiology Case Reports)
Niemann-Pick disease (NPD) is an autosomal recessive disease caused by deficient lysosomal enzyme or faulty cholesterol transport. A 9-year-old male patient presented with 6 years of abdominal swelling, previously treated as tuberculosis. He exhibited hepatosplenomegaly, delayed growth, and pancytopenia. Imaging revealed hepatosplenomegaly, a focal splenic infarct, diffuse interstitial septal thickening, and ground glass opacities in the lungs, raising suspicion of a storage disease. Further biopsies, of the bone marrow and liver, revealed the presence of foam cells with abundant multivacuolated cytoplasm and central round nuclei, suggesting NPD. Genetic testing and specific enzyme activity tests are unavailable in our setting. This case highlights the diagnostic challenges of rare disease in resource-limited settings, often mistaken for more common conditions like tuberculosis and lymphoma.